Brain functional connectivity analysis in patients with relapsing-remitting multiple sclerosis: A graph theory approach of EEG resting state - Shirani, Sepehr; Mohebbi, Maryam (Frontiers in Neuroscience, 2022)
Multiple sclerosis (MS) is an autoimmune disease related to the central nervous system (CNS). This study aims to investigate the effects of MS on the brain's functional connectivity network using the electroencephalogram (EEG) resting-state signals and graph theory approach. Resting-state eyes-closed EEG signals were recorded from 20 Relapsing-Remitting MS (RRMS) patients and 18 healthy cases. Here, the prime objective is to calculate the connectivity between EEG channels to assess the differences in brain functional network global features. The results demonstrated lower cortical activity in the Alpha and higher activity for the Gamma frequency bands in RRMS patients compared to the healthy group. Here, graph metric calculations revealed a significant difference in the diameter of the functional brain network based on the Directed Transfer Function (DTF) measure between the two groups indicating a higher diameter in RRMS cases for the Alpha frequency band. A higher diameter for the functional brain network in MS cases can result from anatomical damage. In addition, considerable differences between the networks' global efficiency and transitivity based on the imaginary part of coherence (iCoh) measure were observed, indicating higher global efficiency and transitivity in the Delta, Theta, and Beta frequency bands for RRMS cases, which can be related to the compensatory functional reaction from the brain. This study indicated that in RRMS cases, some of the global characteristics of the brain's functional network, such as diameter and global efficiency, change and can be illustrated even in the resting state condition when the brain is not under cognitive load.